2016
DOI: 10.3233/bsi-160148
|View full text |Cite
|
Sign up to set email alerts
|

The early development and application of FTIR difference spectroscopy to membrane proteins: A personal perspective

Abstract: Abstract. Membrane proteins facilitate some of the most important cellular processes including energy conversion, ion transport and signal transduction. While conventional infrared absorption provides information about membrane protein secondary structure, a major challenge is to develop a dynamic picture of the functioning of membrane proteins at the molecular level. The introduction of FTIR difference spectroscopy around 1980 to study structural changes in membrane proteins along with a number of associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 240 publications
(274 reference statements)
0
11
0
Order By: Relevance
“…Low-temperature spectroscopic studies have previously been extensively performed on a variety of microbial rhodopsins and provided important information. For example, the ability to trap or partially block the decay of photocycle intermediates offers a means to characterize their spectral properties for example by the application of resonance Raman, FTIR, UV–visible, and NMR. In conjunction with the ability to crystallize some microbial rhodopsin such as BR, low temperatures provide a way to trap these proteins in pure or mixtures of different photointermediates that can be analyzed in parallel by both spectroscopy and X-ray crystallography …”
Section: Discussionmentioning
confidence: 99%
“…Low-temperature spectroscopic studies have previously been extensively performed on a variety of microbial rhodopsins and provided important information. For example, the ability to trap or partially block the decay of photocycle intermediates offers a means to characterize their spectral properties for example by the application of resonance Raman, FTIR, UV–visible, and NMR. In conjunction with the ability to crystallize some microbial rhodopsin such as BR, low temperatures provide a way to trap these proteins in pure or mixtures of different photointermediates that can be analyzed in parallel by both spectroscopy and X-ray crystallography …”
Section: Discussionmentioning
confidence: 99%
“…In the mid-twentieth century, first studies appeared that demonstrated the large potential of infrared (IR) spectroscopy for protein research [1,2]. These days, IR spectroscopy has steadily been among methods for studying protein structures at the different levels of their organization [3][4][5][6][7]. In protein studies, IR spectroscopy is predominantly used as part of absorption spectroscopy techniques (i.e., for measuring absorption spectra).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported the effective usage of FTIR in the characterization of recombinant protein secondary structure elements. 40 , 41 It is worth noting that the most subtle spectral region of a protein secondary structural component is the amide I band, which is usually within 1700−1600 cm −1 ; it is a result of the C = O stretch vibrations of the peptide linkages, which make up approximately 80% of a protein. The frequencies of the amide I band constituents are established to be correlated meticulously to every secondary structural element of a protein.…”
Section: Discussionmentioning
confidence: 99%